PET/CT in Cancer - Beheshti, Mohsen; Langsteger, Werner; Rezaee, Alireza; ScienceDirect eBooks (Saintt Louis : Elsevier Health Sciences, 2017)
Edited, authored, and reviewed by an expert team of oncologists and nuclear physicians/radiologists, this one-of-a-kind title helps you make the most of the critical role PET/CT plays in cancer staging and therapeutic responses to individualized treatments. Drs. Mohsen Beheshti, Werner Langsteger, and Alireza Rezaee place an emphasis on cutting-edge research and evidence-based practice, ensuring that you're up to date with every aspect of this fast-changing field. For each tumor entity, you'll find authoritative discussions of background, pathology, common pattern of spread, TNM classification, clinical guidelines, discussion, evidence-based recommendations, key points, and pitfalls.
Case 5: Staging Lung Cancer-Guiding Biopsy and RadiotherapyCase 6: Staging SCLC-Differentiation of Limited From Extended Stage; Case 7: NSCLC-Recurrence; Case 8: Mesothelioma-Treatment Monitoring; Case 9: Talc Pleurodesis; Case 10: Carcinoid Tumor-Very Low FDG-Avid Malignancies; REFERENCES; 3 -- Breast Cancer; BACKGROUND; General1,2; Early Clinical Symptoms1,3; Primary Diagnostic Procedures1,4; Standard Treatment5; Prognostic Factors6; Five-Year Survival7; TUMOR CHARACTERISTICS AND TYPICAL BEHAVIOR; Histopathology8; Distribution and Localization9-11; N-lymph nodes; T-primary.
Print version record.
M-distant metastasis.
Includes bibliographical references and index.
Elsevier
Keywords: Cancer -- Imaging; Oncology; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Cancer -- Imaging; Oncology; Electronic books